Increasing Learning Outcomes and Ability Critical Thinking of Students Through Application Problem Based Learning Strategies - Lubis, Rahmat Rifai; Irwanto, Irwanto; Harahap, Muhammad Yunan (Universitas Malikussaleh, 2019)
Classroom action research aims to determine the improvement of critical thinking skills and student learning outcomes in the Faraidh material fiqh lessons. The research location is MTS. Medan PAI in class IX. This research was conducted in 3 cycles. Each cycle consists of Planning, Implementation, Observation, and Reflection. The results showed an increase in student learning from Cycle I, II, III. Research results show that in Cycle I: Scores of 90-100 (30%), 80-89 (50%), 70-79 (10%), 60-69 (10%), <59 (0%), At Cycle II, Score Range 90-100 (40%), 80-89 (40%), 70-79 (15%), 60-69 (5%), <59 (0%), In Cycle III. Scores of 90-100 (60%), 80-89 (40%), 70-79 (0%), 60-69 (0%), <59 (0%). The results of the study also showed that there was an increase in students' thinking skills which was characterized by several indicators namely Find and formulate problems, Analyzing problems, Expressing criticism and ideas, Presentation of solutions.